FROM CHRONIC SINUSITIS TO SINONASAL TUMORS: THE EXPANDING ROLE OF FESS IN MODERN SURGERY - Aleksandra Kaźmierczyk,; Jędrzej Kęsik,; Daria Madycka,; Małgorzata Słaboń,; Karol Stępniak,; Wiktor Telega,; Kinga Wnuczek,; Joanna Wrona,; Weronika Skrzypek,; Jan Wojtas, (International Journal of Innovative Technologies in Social Science, 2025)
Objective: The objective of this study was to explore the evolving role of Functional Endoscopic Sinus Surgery (FESS) - the gold standard in the treatment of chronic rhinosinusitis and other sinus diseases. Advances in diagnostic imaging, surgical instruments, and navigation systems have significantly improved the safety and efficacy of this technique. This study provides an overview of the FESS technique, and its expanding indications - application in the treatment of selected sinus tumors, such as inverted papilloma, juvenile nasopharyngeal angiofibroma (JNA), and osteomas.Methods: A narrative review of the literature was conducted, focusing on the development of FESS, its surgical technique, safety profile, and clinical outcomes. Special attention was given to its comparison with traditional open approaches in both inflammatory and neoplastic conditions of the sinonasal tract.Key Findings: The analysis revealed that technological progress - particularly in diagnostic imaging, surgical instruments, and intraoperative navigation - has significantly improved the precision and safety of FESS. Clinical evidence demonstrates that endoscopic resection of sinonasal tumors often achieves recurrence rates equal to or lower than those associated with open surgery, while minimizing morbidity, hospitalization time, and facial disfigurement. Successful outcomes depend on appropriate patient selection, meticulous preoperative planning, and the surgeon’s expertise.Conclusions: Functional Endoscopic Sinus Surgery is a safe and effective modality for treating a wide range of sinonasal diseases, including chronic rhinosinusitis and selected benign tumors. With proper patient selection, preoperative planning, and surgical expertise, FESS offers substantial benefits over traditional open approaches, including reduced morbidity and improved recovery. Continued technological advancements and long-term outcome studies will further refine its role in comprehensive sinonasal care.